Clinical and Histopathological Evaluation of a Rabbit Model for Pythium insidiosum Keratitis. (3rd May 2020) - Kalra, Paavan; Ahirwar, Lalit Kishore; Mittal, Ruchi; Ranjith, Konduri; Das, Shilpa; Manjulatha, Kodiganti; Bagga, Bhupesh; Mohamed, Ashik; Joseph, Joveeta; Sharma, Savitri
ABSTRACT: Purpose : To describe the clinical characteristics and histopathological features in a rabbit model of Pythium insidiosum keratitis. Methods : Zoospores of P. insidiosum isolated from a patient with microbial keratitis were used for inoculation of the right eye of 48 New Zealand White rabbits in either low (LD) or high dose (HD). Apart from variable dosage the rabbits were grouped (6 rabbits per group) based on route of inoculation (topical on abraded cornea or intracorneal) and immunosuppression (subconjunctival steroid or no steroid). Left eye received phosphate buffered saline via route similar to the right eye. Daily clinical examination of the eye was done, the corneas were harvested on day 3, 7 and 9 and part of the cornea was preserved in 10% neutral buffered formalin for histopathological examination. Results : Left eye of all rabbits were clinically normal. Eyes with intracorneal injection of zoospores developed infection irrespective of dose of inoculation and administration of steroids. One of the consistent early signs of infection was ring like infiltrate in the peripheral cornea. On day 2, rabbits receiving HD developed significantly greater inflammation compared to LD [median clinical score in HD- 11 (IQR = 10–12), versus 9 (IQR = 8–9) in LD ( p = 0.004)]. The density of inflammation showed temporal correlation (increase with time) when the inoculum was low. Of the rabbits that received topical inoculation one rabbit cornea showed mild infiltrate in steroid group while no eye was infected in the group without steroid. Sparsely septate to aseptate branching filaments were noted in the stroma of all infected corneas. Conclusions : We describe the first animal model of Pythium keratitis that holds promise for future studies. While topical inoculation of zoospores was unsuccessful in causing infection intracorneal inoculation without immunosuppression was sufficient to develop clinically severe keratitis in rabbits.